Simple and low-cost technology for irrigation from shallow aquifers in the Western Terai, Nepal - Faillace, Costantino (Journal of Nepal Geological Society, 2000)
The paper briefly outlines the hydrogeological conditions of the Terai area and describes the simple and low -cost drilling technologies used over the past thirty years in developing its groundwater resources for irrigated agriculture. The results herewith presented derive from the author's personal experience of the area and from the review of numerous studies and researches, most of which are reported in the references. The Terai area is a very rich groundwater reservoir, made up of thick alluvial deposits transported in the lowlands by a number of watercourses originating in the northern hilly and mountainous areas. Proceeding from north to south, the alluvial deposits become progressively finer and inter-finger with each other. It is the most productive area of Nepal with rice and wheat as main food grains. The irrigated areas of the Terai Plain can be further expanded using simple and low-cost shallow tube wells drilled manually or by machine, and equipped with centrifugal diesel pumps, rower, and treadle pumps. The results of the 40,000 shallow tube wells drilled in the area have proven that shallow aquifer potential is very high, and this justifies the expansion of the present irrigated area to benefit also poor and marginal farmers. The author stresses that the new development strategy should be based not only on the experience gained from the past thirty years, but also on improved technology and on renewed financial input in the forthcoming projects. For a well-coordinated development of the area, it will be necessary to adopt a model in which the people will be fully involved in the planning as well in the implementation, and also participate in the operation and maintenance of wells and irrigation water systems. The new development strategy should aim at expanding progressively the present irrigated area to cope with the rate of the population growth.